Development of Newton Gravity Student Worksheets on Problem-Based Learning Model to Improve Students' Scientific Argumentation Skills - Dhila Linggar Lentika; Setyo Admoko (IKIP Mataram, 2022)
The purpose of this study was to evaluate the validity, practicability, and efficiency of student worksheets for improving students' scientific argumentation skills on the topic of Newton's Law of Gravity. This study was conducted using the 4-D method, which consists of four stages of research: define, design, develop, and disseminate. It is restricted to the development stage in this study. The validity of the student worksheets was analysed based on aspects of content feasibility, guidelines, questions, scientific argumentation skills, and the Problem Based Learning model achieved an overall percentage of 93.75 %, 100 %, and 95.83 % respectively. 100 %, 100 %, 100 %. The practical aspect of student worksheets is analyzed based on the students' feedback in terms of the student worksheets component, Problem Based Learning model, enthusiasm, Newton's Law of Gravity topic, and scientific argumentation, with an average of 86 %, 82 %, 91.5 %, 88.5 %, and 88 % with robust criteria, respectively. The effectiveness of the student worksheets was determined using the outcomes of the scientific argumentation test's pretest and posttest, and they met the criteria for being very effective. The given test received an average n-gain score of 0.7342 in the interpretation category. Based on the research findings of the data analysis for validity, practicability, and effectiveness, it is possible to conclude that the student worksheets developed are feasible and effective in improving students' argumentation skills. Student worksheets based on a similar Problem Based Learning model could be designed to improve students' argumentation skills on other physics topics.